(untitled) - Wisker, Gina (New York, 2005)
The Good Supervisor engages readers in dialogue and active reflection on the strategies of effective supervision of PhDs, postgraduate and undergraduate research. Accessibly written, it encourages supervisors to reflect on and enhance their research supervision practice with a diversity of students on a variety of research projects: Postgraduate and undergraduate levels, international and distance students; practice and professional research; research leading to creative process and products/creations; the PhD by publication; supervising your colleagues; interpersonal skills; managing diversity in learning styles, gender, age and culture. The book is also useful for students undertaking research. There is special focus on research skills development.and on supporting students through and beyond the examination process
Keywords: Graduate students,Faculty advisors,Dissertations, Academic,Doctor of philosophy degree; Supervision